Мальчик и Девочка из спичечной коробки - Кестнер Эрих (Антиква, 2001)
Экземпляры: ф.18 (20200617) / Инвентарный номер: 3402 / Цена: / Сис.шифр: 84(4Гем)-4 / Авт.знак: К 36 / ГРНТИ: 17.82.93 / ББК: 84(4Гем)-4